Contributions of the geotechnology to monitoring of soybean farming in Assis Chateaubriand, Parana (PR), Brazil - Rizato, Matheus [UNESP]; Zacharias, Andrea Aparecida [UNESP] (Univ Andes, Inst Geografia & Conservacion Recursos Naturales, 2019)
Soy has emerged in recent years as the main crop agroexport in Brazil, encouraging their expansion and influencing global agricultural dynamic. In this context, this research aims to demonstrate that the geotechnology contribute to monitoring the evolution of agricultural products. Therefore, by using Landsat satellite images, we sought to identify and quantify areas of soybean crop in 2008/09 and 2010/11 in Assis Chateaubriand - Parana/PR, Brazil. It is concluded that the geotechnology assist in monitoring temporo-spatial agricultural products such as soybeans during the season, including generating data that can give support for the analysis of economic behavior culture.
Keywords: geotechnology; landsat; remote sensing; geographic information systems; soybeans